The responsibility of the administration in compliance with the going concern assumption during the preparation for their financial statements: Research practically at muster of companies (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to demonstrate the impact of the going concern assumption in different accounting applications to provide a realistic look and more accurate result of activity and financial situation, as well as determining the responsibility of the Company's administration in compliance with the going concern assumption during the preparation for their financial statements, and to clarify the concept of integration between internal audit and external audit about going concern assumption, besides its importance and usefulness on the work of both of the internal auditor and the external auditor, as well as on the company under auditing process.This research purports preparing an internal audit program, including a set of auditing actions to verify the use of management in order to going concern assumption in the preparation of its financial statements.To achieve the above objectives, the research has tended theoretically to employ different views for a number of authors and researchers, while the research practically has sought a number of companies in order to clarify the extent of the commitment of the company's administration in going concern assumption in its preparation for the financial statements based on the international& local standards and laws and regulations for the purpose of giving a realistic and accurate results about the financial status.